2017
DOI: 10.1080/10942912.2016.1258575
|View full text |Cite
|
Sign up to set email alerts
|

Volatile components of white Hypsizygus marmoreus detected by electronic nose and HS-SPME-GC-MS: Influence of four drying methods

Abstract: Four drying methods, viz hot air drying (HD), vacuum drying (VD), microwave-vacuum drying (MVD), and vacuum freeze-drying (FD), were used to dry white Hypsizygus marmoreus (WHM). The volatile and taste components of the dried WHM were comparatively analysed by electronic nose technology (E-nose) and head-space solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GS-MS). Principal component analysis (PCA) showed that E-nose could distinguish fresh WHM and four dried products c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Chen et al. () reported that the most dominant volatile compounds of the fresh white beech mushroom were 1‐octen‐3‐ol (32.97%), followed by 3‐octanone (11.86%), and t‐2‐octenal (6.18%) in decreasing order, as determined by HS‐SPME‐GC‐MS. Our result also showed that 1‐octen‐3‐ol and t‐2‐octenal were the most abundant volatiles, but not 3‐octanone in white beech.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al. () reported that the most dominant volatile compounds of the fresh white beech mushroom were 1‐octen‐3‐ol (32.97%), followed by 3‐octanone (11.86%), and t‐2‐octenal (6.18%) in decreasing order, as determined by HS‐SPME‐GC‐MS. Our result also showed that 1‐octen‐3‐ol and t‐2‐octenal were the most abundant volatiles, but not 3‐octanone in white beech.…”
Section: Resultsmentioning
confidence: 99%
“…But in our study, 2,3,6-trimethylpyridine was not identified in white beech mushrooms. Chen et al (2017) reported that the most dominant volatile compounds of the fresh white beech mushroom were 1-octen-3-ol (32.97%), followed by 3-octanone (11.86%), and t-2-octenal (6.18%) in decreasing order, as determined by HS-SPME-GC-MS. Our result also showed that 1-octen-3-ol and t-2-octenal were the most abundant volatiles, but not 3-octanone in white beech. Button mushroom had exceptionally high level of benzaldehyde and benzyl alcohol (Table 1 and Figure 2).…”
Section: Volatile Compound Profiles In Mushroom Speciesmentioning
confidence: 98%
See 2 more Smart Citations
“…Umami substances can be found in all kinds of food including vegetables, cheese, meat, and seafood, and they are also a typical taste in mushrooms. Except for the nonvolatile components, the aroma of mushrooms also plays an important role in the sensory attributes and consumer acceptance . In L. edodes , the fragrance was mainly contributed by volatile compounds, most of which were made up of about six kinds of compounds, namely alcohols, sulphide, ketones, aldehydes, esters, and hydrocarbon.…”
Section: Introductionmentioning
confidence: 99%